Dynamic Resource Allocation in Cognitive Radio Networks – Priority Scheduling approach: Literature Survey - Tamilarasan, S; Kumar, P (International Journal of Computer Sciences and Engineering, 2025)
In this paper we presents a comprehensive literature survey of cognitive radio technology, focusing on its application to dynamic resource allocation, based on priority scheduling approach. Dynamic spectrum access provides resource sharing between primary users called licensed users (PUs) and Secondary Users called unlicensed users (SUs). An essential examination test is that in what capacity ought to be apportioned or relegated accessible unused range to unlicensed clients. The fitting bit of unmoving repeat range existing together learned radios while enhancing hard and fast transmission limit usage furthermore minimizing impedance is required for the profitable extent use in CRN. The system for settled extent segment came to fruition to less range utilization over the entire reach. In this paper we presented the different approaches used for dynamic resource allocation and scheduling in heterogeneous Cognitive radio networks.